IoT-Based Plant Irrigation Information Management System - Jagathison, Diveadarsini; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2025)
Efficient irrigation is crucial for maintaining the health and growth of plants, particularly in regions experiencing unpredictable rainfall. Proper water management promotes optimal plant growth and addresses concerns about water usage and rising costs. Hence, this study proposes an IoT-Based Plant Irrigation Information Management System to monitor real-time soil moisture levels, weather conditions, and plant water requirements. The case study was conducted at Anna Nursery and utilized the newly built system. Integrating sensors and data analytics, the system provides automated irrigation solutions that optimize water usage while ensuring plants receive adequate moisture. The new system provides several essential modules such as user registration and login, sensor and data collection, control and automation, water usage tracking, and report analysis. The system was developed using Agile methodology, the PHP programming language, and the XAMPP database. The agile method facilitates iterative progress through small, incremental changes, which allow teams to respond quickly to changing requirements and user feedback. The use of PHP and XAMPP enables a robust back-end infrastructure that supports efficient data storage and processing; the implementation of this system in production nurseries aims to enhance crop health, increase production efficiency and reduce operational costs associated with water use. This approach promotes sustainable agricultural practices and enhances the profitability of nursery operations by ensuring that water is used appropriately.